2019
DOI: 10.12688/f1000research.18492.1
|View full text |Cite
|
Sign up to set email alerts
|

Progress in perceptual research: the case of prosopagnosia

Abstract: Prosopagnosia is an impairment in the ability to recognize faces and can be acquired after a brain lesion or occur as a developmental variant. Studies of prosopagnosia make important contributions to our understanding of face processing and object recognition in the human visual system. We review four areas of advances in the study of this condition in recent years. First are issues surrounding the diagnosis of prosopagnosia, including the development and evaluation of newer tests and proposals for diagnostic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 132 publications
1
21
0
2
Order By: Relevance
“…Recognizing faces is a highly specialized, multistage process (Bruce & Young, 1986) that involves a network of brain regions (Grill-Spector et al, 2017;Haxby et al, 2000;Haxby & Gobbini, 2011). Though recognition of familiar faces is typically rapid and effortless (Jenkins et al, 2018), this ability can be severely impaired in many neurological, psychiatric, and developmental disorders including prosopagnosia (Albonico & Barton, 2019;Mayer & Rossion, 2007), autism spectrum disorders (Dwyer et al, 2019;Weigelt et al, 2012), Alzheimer's disease (Lavallée et al, 2016), person recognition disorders (Gainotti, 2007), as well as others (Barton et al, 2004;Dimitriou et al, 2015). The causes of face recognition deficits in these conditions vary considerably, and it is crucial to identify measures that can discern the stages of face identification impairments to help with both diagnosis (Benton & Van Allen, 1968;Benton et al, 1994;Duchaine & Nakayama, 2006;Duchaine et al, 2007) and treatment (Bate & Bennetts, 2014;DeGutis et al, 2014b, a).…”
Section: Introductionmentioning
confidence: 99%
“…Recognizing faces is a highly specialized, multistage process (Bruce & Young, 1986) that involves a network of brain regions (Grill-Spector et al, 2017;Haxby et al, 2000;Haxby & Gobbini, 2011). Though recognition of familiar faces is typically rapid and effortless (Jenkins et al, 2018), this ability can be severely impaired in many neurological, psychiatric, and developmental disorders including prosopagnosia (Albonico & Barton, 2019;Mayer & Rossion, 2007), autism spectrum disorders (Dwyer et al, 2019;Weigelt et al, 2012), Alzheimer's disease (Lavallée et al, 2016), person recognition disorders (Gainotti, 2007), as well as others (Barton et al, 2004;Dimitriou et al, 2015). The causes of face recognition deficits in these conditions vary considerably, and it is crucial to identify measures that can discern the stages of face identification impairments to help with both diagnosis (Benton & Van Allen, 1968;Benton et al, 1994;Duchaine & Nakayama, 2006;Duchaine et al, 2007) and treatment (Bate & Bennetts, 2014;DeGutis et al, 2014b, a).…”
Section: Introductionmentioning
confidence: 99%
“…Capgras delusion can occur due to 'spatial disorientation, anatomic disconnection, memory and executive process impairment, and loss of ego' [4]. While psychodynamic theories consist of ambivalence theory, depersonalization theory, and regression theory, neurocognitive hypotheses focus on right hemispheric dysfunction, face-recognition processing abnormalities, and focal structural cerebral abnormalities [29]. There are two components of the visual recognition of a familiar face, one of which is responsible for conscious recognition of the face and the remembrance of associated semantic information, while the other is responsible for the limbic-mediated emotional arousal including the feeling of familiarity that accompanies the conscious recognition of a known face [9].…”
Section: Explanations For Capgras Syndromementioning
confidence: 99%
“…The term CS does not demonstrate a well-defined mental disorder. Over the years various studies have suggested psychodynamic and neurophysiological interpretations for CS, and various aetiologies have been recommended for the condition's development [16,18,29].…”
Section: Neuropsychological Assessment For Capgras Syndromementioning
confidence: 99%
See 2 more Smart Citations